2016
DOI: 10.1016/j.actbio.2016.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic hydrogel with tunable mechanical properties for vitreous substitutes

Abstract: The vitreous humor of the eye is a biological hydrogel principally composed of collagen fibers interspersed with hyaluronic acid. Certain pathological conditions necessitate its removal and replacement. Current substitutes, like silicone oils and perfluorocarbons, are not biomimetic and have known complications. In this study, we have developed an in situ forming two-component biomimetic hydrogel with tunable mechanical and osmotic properties. The components are gellan, an analogue of collagen, and poly(methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 24 publications
3
67
0
Order By: Relevance
“…EWCs of the PNAGA and PNAGA‐PCBAA hydrogels were measured at room temperature by using a gravimetric method reported earlier 41. The refractive indexes of PNAGA and PNAGA‐PCBAA hydrogels were determined on an Abbe refractometer (WYA‐2W, Lumsail Industrial Inc., Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…EWCs of the PNAGA and PNAGA‐PCBAA hydrogels were measured at room temperature by using a gravimetric method reported earlier 41. The refractive indexes of PNAGA and PNAGA‐PCBAA hydrogels were determined on an Abbe refractometer (WYA‐2W, Lumsail Industrial Inc., Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, thanks to its versatility, gellan gum is attracting increasing interest in the biomedical field and is being proposed for tissue engineering and regenerative medicine applications (Coutinho et al, 2010;Santhanam et al, 2016). A pioneering study by Shoichet et al exploited a gellan gum matrix to support the adhesion and proliferation of neural stem cells, showing that the peptide-modified gellan gum, together with the olfactory ensheathing glia, enhanced neural stem/progenitor cell survival (Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are 3D structures comprising crosslinked polymers and water, and have been utilized in a variety of tissue engineering applications 20–22. Since hydrogels resemble natural ECM structurally and compositionally, they provide a microenvironment to cells for effective adhesion, proliferation, and invasion 23–26. Several hydrogels have been used as an effective scaffold for the delivery of cells and/or signals for tissue regeneration and tissue model 27,28.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Since hydrogels resemble natural ECM structurally and compositionally, they provide a microenvironment to cells for effective adhesion, proliferation, and invasion. [23][24][25][26] Several hydrogels have been used as an effective scaffold for the delivery of cells and/or signals for tissue regeneration and tissue model. [27,28] For example, Kim et al demonstrated that bone morphogenetic protein-2 (BMP-2) incorporated thiolated gelatin and poly(ethylene glycol) diacrylate (PEGDA) composite hydrogel scaffold could exhibit effective regeneration of calvarial bone in a rat model.…”
Section: Introductionmentioning
confidence: 99%